2001
DOI: 10.1002/ppul.2009.abs
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of lung disease in children with cystic fibrosis after Pseudomonas aeruginosa acquisition

Abstract: As part of the ongoing Wisconsin Cystic Fibrosis (CF) Neonatal Screening Project, we had the unique opportunity to study the longitudinal relationship between Pseudomonas aeruginosa (Pa) acquisition and infection and developing lung disease in children with CF. The primary objective was to determine whether acquisition of Pa was associated with a measurable change in the progression of lung disease. Two outcome measures were used to study 56 patients who were diagnosed through newborn screening: 1) Wisconsin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
244
3
9

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(265 citation statements)
references
References 0 publications
9
244
3
9
Order By: Relevance
“…However, we speculate that changes in ASL pH might contribute, in part, to variations in the species of bacteria that infect CF airways. For example, S. aureus is commonly cultured early and P. aeruginosa is cultured later in the course of CF airway disease in humans and pigs (46,47,75). Interestingly, a reduced pH impaired hBD-3 killing of S. aureus, but had minor effects on killing of P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…However, we speculate that changes in ASL pH might contribute, in part, to variations in the species of bacteria that infect CF airways. For example, S. aureus is commonly cultured early and P. aeruginosa is cultured later in the course of CF airway disease in humans and pigs (46,47,75). Interestingly, a reduced pH impaired hBD-3 killing of S. aureus, but had minor effects on killing of P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that young age at initial P. aeruginosa acquisition is an important risk factor for the development of more severe CF lung disease (6,(31)(32)(33). It is likely that the earlier acquisition of P. aeruginosa allows more time for phenotypes to develop that are associated with pulmonary exacerbations and/or lower FEV 1 % predicted, for example, mucoidy (34,35).…”
Section: Original Researchmentioning
confidence: 99%
“…The aim of this study was to determine the effects of PMA treatment on bacterial community characteristics (abundance, diversity, composition and structure), as analysed by 16S rRNA gene pyrosequencing, total bacterial Q-PCR enumeration and species-specific Q-PCR enumeration of Pseudomonas aeruginosa, a clinically important pathogen in CF airway disease (Ballmann et al, 1998;Kosorok et al, 2001). Comparisons were made first between paired PMA-treated and non-PMA-treated samples (that is, the local community level), before focusing on core and satellite groups of bacterial taxa within the entire collection of PMA-and non-PMA-treated samples (that is, the metacommunity).…”
Section: Introductionmentioning
confidence: 99%